MODELING OF AN AIRCRAFT CONSTANT SPEED DRIVE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The constant speed constant frequency (CSCF) alternative current electrical power system of an aircraft is based on a constant speed drive (CSD). This type of electrical power system is used on most modern aircraft due to its high inherent reliability and long life characteristic. This paper presents the design and simulation of an aircraft constant speed drive using the Simscape package of Simulink, a MATLAB program
Keywords: Constant speed drive; Synchronous generator; Hydraulic unit; Proportional integral derivative controller